1999
DOI: 10.1051/limn/1999022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamique du phytoplancton en relation avec certains paramètres physico-chimiques dans la retenue El Kansera (Maroc)

Abstract: Mots-clés : phytoplancton, dynamique, cyanobactéries, diatomées, retenue de barrage. L'étude de la dynamique saisonnière du phytoplancton dans la retenue El Kansera a été réalisée dans le but de comprendre au mieux le phénomène d'eutrophisation de cet écosystème lacustre. La biomasse (exprimée en poids frais) a été suivie pendant un cycle et demi, d'avril 1995 à août 1996. Cette période étant marquée par la transition d'une année de sécheresse avec une année pluvieuse, la composition et la dynamique saisonnièr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The Youssef Ben Tachafine dam is subject to harsh climatic conditions due to the succession of acute drought cycles. Work carried out on the quality of Moroccan lakes under climatic conditions similar to those of the YBT dam [3,4], has shown that drought has caused significant changes in the general quality of the aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The Youssef Ben Tachafine dam is subject to harsh climatic conditions due to the succession of acute drought cycles. Work carried out on the quality of Moroccan lakes under climatic conditions similar to those of the YBT dam [3,4], has shown that drought has caused significant changes in the general quality of the aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%